Immune suppressive effect of cinnamaldehyde due to inhibition of proliferation and induction of apoptosis in immune cells: implications in cancer. - Franziska Roth-Walter (Public Library of Science (PLoS), 2014)
Background Besides its anti-inflammatory effects, cinnamaldehyde has been reported to have anti-carcinogenic activity. Here, we investigated its impact on immune cells. Methods Activation of nuclear factor-κB by cinnamaldehyde (0-10 µg/ml) alone or in combination with lipopolysaccharide was assessed in THP1XBlue human monocytic cell line and in human peripheral blood mononuclear cells (PBMCs). Proliferation and secretion of cytokines (IL10 and TNFα) was determined in primary immune cells and the human cell lines (THP1, Jurkat E6-1 and Raji cell lines) stimulated with cinnamaldehyde alone or in conjunction with lipopolysaccharide. Nitric oxide was determined in mouse RAW264.7 cells. Moreover, different treated PBMCs were stained for CD3, CD20 and AnnexinV. Results Low concentrations (up to 1 µg/ml) of cinnamaldehyde resulted in a slight increase in nuclar factor-kB activation, whereas higher concentrations led to a dose-dependent decrease of nuclear factor-kB activation (up to 50%) in lipopolysachharide-stimulated THP1 cells and PBMCs. Accordingly, nitric oxide, interleukin 10 secretion as well as cell proliferation were reduced in lipopolysachharide-stimulated RAW264.7 cells, PBMCs and THP1, Raji and Jurkat-E6 immune cells in the presence of cinnamaldehyde in a concentration-dependent manner. Flow cytometric analysis of PBMCs revealed that CD3+ were more affected than CD20+ cells to apopotosis by cinnamaldehyde. Conclusion We attribute the anti-inflammatory properties of cinnamaldehyde to its ability to block nuclear factor-κB activation in immune cells. Treatment with cinnamaldehyde led to inhibition of cell viability, proliferation and induced apoptosis in a dose-dependent manner in primary and immortalized immune cells. Therefore, despite its described anti-carcinogenic property, treatment with cinnamaldehyde in cancer patients might be contraindicated due to its ability to inhibit immune cell activation.